A meta-analysis of the impact of situationally induced achievement goals on task performance - van Yperen, N. W.; Blaga, M.; Postmes, T. (Human Performance, 2015)
The purpose of this research was to meta-analyze studies which experimentally induced an achievement goal state to examine its causal effect on the individual`s performance at the task at hand, and to investigate the moderator effects of feedback anticipation and time pressure. The data set comprised 19 papers, 79 individual effect sizes, and 3,482 participants. Performance measures represented task performance across a variety of tasks. The findings indicate that relative to avoidance goals (either performance-avoidance goals or mastery-avoidance goals), approach goals (either mastery-approach goals or performance-approach goals) enhance task performance. Furthermore, relative to performance-approach goals, mastery-approach goals lead to better performance, particularly when individuals do not anticipate feedback and when there is no time pressure. Implications and future directions for research are discussed.